Piston ring and method for manufacturing the same

By forming the Si and N content film under specific conditions on the piston ring, the problems of piston ring wear under high output and exhaust gas limitation are solved, and a piston ring with high peel resistance, crack resistance and wear resistance are achieved. Suitable for harsh engine environments.

CN115003936BActive Publication Date: 2025-01-17RIKEN CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180009792.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-27
Filing Date
2021-01-21
Publication Date
2025-01-17
Estimated Expiration
2041-01-21

AI Technical Summary

Technical Problem

Under high output and exhaust gas restrictions, the use environment becomes harsh, resulting in an increase in wear and peel resistance. The existing film has shortcomings in wear resistance and peel resistance, especially in the thinning of the oil film and the increase in heat load. It is difficult to effectively suppress cracks and peeling in the case.

Method used

The physical vapor deposition method is used to form a film with Si and N content of 1.1 to 7.5 atomic %, a crystallite size of 10 to 30 nm and a compression residual stress of 400 to 800 MPa on the substrate surface of the piston ring, combining moderate hardness and crystallization orientation , a Cr-Si-N-based film can be formed under high pressure and bias voltage conditions, thereby enhancing the peel resistance, crack resistance and wear resistance of the piston ring.

Benefits of technology

The piston ring has a high level of peel resistance, crack resistance and wear resistance, which effectively reduces the wear caused by sliding resistance and thermal load, and extends the service life of the piston ring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115003936B_ABST
    Figure CN115003936B_ABST
Patent Text Reader

Abstract

The manufacturing method of the piston ring of the present invention includes (A) a step of cleaning the surface of the base material of the piston ring, and (B) a step of forming a film containing Si and N by physical vapor deposition in a chamber in a manner covering at least a portion of the surface of the base material, wherein in the step (B), the pressure in the chamber is set in the range of 2 to 6 Pa, and the bias voltage is set in the range of -5 to -18 V in order to form a film satisfying the following conditions. <Conditions of the film> · The amount of Si is in the range of 1.1 to 7.5 atomic %. · The crystallite size is in the range of 10 to 30 nm. · The compressive residual stress is 400 to 800 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a piston ring and a method for manufacturing the same. Background Art

[0002] Piston rings are used in engines of automobiles and the like. The piston rings are mounted in grooves provided on the outer peripheral surface of the piston. Piston rings are required to contribute to higher engine performance and lower fuel consumption by utilizing properties such as wear resistance and seizure resistance. Various efforts have been made to improve the wear resistance of piston rings.

[0003] For example, the invention described in Patent Document 1 is designed to provide a sliding member having excellent wear resistance even under severe conditions in an engine using direct fuel injection or exhaust gas recirculation (EGR). The sliding member is formed by a substrate covered with a film, and the film is formed by a mixed structure of a crystalline phase and an amorphous phase composed of a metal nitride, a metal carbide, or a metal carbonitride.

[0004] The invention described in Patent Document 2 is made to provide a piston ring for an internal combustion engine having both wear resistance and crack resistance / peeling resistance. The piston ring has a hard film formed on at least the outer peripheral sliding surface, and the hard film is composed of a crystal phase having Cr, N and Si as constituent elements, having the same crystal structure as CrN, and having a Si atomic ratio of 1% or more and 9.5% or less in the crystal lattice.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2002-266697

[0008] Patent Document 2: Japanese Patent Application Publication No. 2008-14228 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In recent years, in order to cope with the high output of engines and exhaust gas regulations, for example, the combustion temperature is being raised, low viscosity lubricants are being adopted, and the amount of oil is being reduced. As a result, the use environment of piston rings is becoming more severe year by year and has become a boundary lubrication environment, and the increase in the amount of wear of piston rings has become a problem. This is mainly due to the increase in resistance during sliding and the increase in heat load caused by the thinning of the oil film.

[0011] Both Patent Documents 1 and 2 disclose forming a coating by ion plating. The CrN-based coating, TiN-based coating, or a laminated coating thereof obtained by ion plating improves the wear resistance and peeling resistance of the piston ring. However, if it is assumed that the use environment of the piston ring will become more severe in the future, there is still room for improvement in the wear resistance and peeling resistance of these coatings.

[0012] The inventors developed a coating in which Si is added to CrN in about 2002. It is known that the coating in which Si is added to CrN (hereinafter referred to as "Cr-Si-N coating" as the case may be) has fine grains due to the addition of Si, and as a result, is dense and has a high hardness. The development policy at that time focused on improving the wear resistance of the coating by increasing the hardness. However, there was a history that cracks generated in the coating could not be fully suppressed and practical application could not be achieved.

[0013] The present invention provides a piston ring provided with a film containing Si and N, and having sufficiently high levels of peeling resistance, crack resistance and wear resistance, and a method for producing the same.

[0014] Methods used to solve problems

[0015] As described above, for example, the hardness of the conventional Cr-Si-N coating is high, but on the other hand, there is a problem that cracks are easily generated in the coating. The cracks in the coating cause peeling. Since the piston ring is exposed to continuous sliding and repeated loads, it is considered difficult to apply the conventional Cr-Si-N coating to the piston ring. However, the inventors repeatedly conducted trial production and evaluation of piston rings, and as a result, determined the conditions of the physical vapor deposition method for forming a coating that can achieve sufficiently high levels of peeling resistance, crack resistance and wear resistance, thereby completing the following invention.

[0016] The manufacturing method of the piston ring of the present invention includes: (A) a process of cleaning the surface of the substrate of the piston ring; and (B) a process of forming a film containing Si and N by physical vapor deposition in a chamber in a manner covering at least a portion of the surface of the substrate. In the process (B), in order to form a film that satisfies the following conditions, the pressure in the chamber is set in the range of 2 to 6 Pa, and the bias voltage is set in the range of -5 to -18 V.

[0017] <Coating conditions>

[0018] The amount of Si is in the range of 1.1 to 7.5 atomic %.

[0019] The crystallite size is in the range of 10 to 30 nm.

[0020] ·Compressive residual stress is 400~800MPa.

[0021] The pressure condition in the chamber (2 to 6 Pa) allows a higher pressure than the conventional film forming condition of the Cr-Si-N film, and the absolute value (5 to 18) of the bias voltage condition (-5 to -18 V) is a smaller value than the conventional film forming condition of the Cr-Si-N film. In the step (B), by forming the film under the conditions satisfying these conditions, a piston ring having sufficiently high levels of peeling resistance, crack resistance, and wear resistance can be manufactured.

[0022] The piston ring of the present invention comprises a substrate and a coating which is provided so as to cover at least a part of the surface of the substrate and contains Si and N, and the coating satisfies the following conditions.

[0023] <Coating conditions>

[0024] The amount of Si is in the range of 1.1 to 7.5 atomic %.

[0025] The crystallite size is in the range of 10 to 30 nm.

[0026] ·Compressive residual stress is 400~800MPa.

[0027] The piston ring can enjoy the advantage of adding Si such as increased hardness by setting the Si content of the film to 1.1 atomic % or more, and can suppress the occurrence of cracks in the film by setting the Si content of the film to 7.5 atomic % or less. These effects are achieved in combination with the crystallite size and compressive residual stress of the film being within the above ranges.

[0028] The hardness of the above-mentioned film is preferably 1000HV0.1 to 1800HV0.1. Although this hardness is softer than the conventional Cr-Si-N series film, it is a sufficient hardness for a piston ring film. The ratio H / E of the hardness H (GPa) of the film measured by a nanoindenter to the Young's modulus E (GPa) of the film is preferably 0.04 to 0.07. When the ratio H / E is within the above range, the film can be elastically deformed appropriately, thereby reducing the Hertz stress generated by sliding and achieving excellent peeling resistance.

[0029] When the composition of the film is represented by Me-Si-N (Me represents a metal element), Me is, for example, Cr. That is, when the film containing Si and N further contains Cr, the amount of Cr is preferably 40 atomic % or more from the viewpoint of suppressing the generation of cracks in the film. In addition, from the viewpoint of suppressing the peeling of the film caused by cracks and their combination, the crystal orientation of the film preferably has a structure coefficient of CrN (111) of 0.4 or more.

[0030] Effects of the Invention

[0031] According to the present invention, there are provided a piston ring provided with a coating containing Si and N, wherein all of the peeling resistance, crack resistance and wear resistance are at sufficiently high levels, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a cross-sectional view schematically showing one embodiment of the piston ring of the present invention.

[0033] Figure 2 It is a schematic diagram showing the structure of a sliding fatigue testing machine. DETAILED DESCRIPTION

[0034] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.

[0035] (Piston ring)

[0036] Figure 1 It is a cross-sectional view schematically showing a piston ring according to the present embodiment. Figure 1 The piston ring 10 shown is a pressure ring for an internal combustion engine (for example, an automobile engine). The pressure ring is installed in a ring groove formed on the side of the piston, for example. The pressure ring is particularly exposed to an environment with high thermal load in the engine.

[0037] The piston ring 10 is annular, for example, with an outer diameter of 40 to 300 mm. The "annular" mentioned here does not necessarily mean a closed circle, and the piston ring 10 may also have a joint. In addition, the piston ring 10 may be a perfect circle or an ellipse when viewed from above. Figure 1 The cross section shown is approximately rectangular, and the sliding surface 10F may also have rounded corners that expand outward.

[0038] The piston ring 10 includes a base material 1 and a coating 5 provided on the outer peripheral surface (surface corresponding to the sliding surface 10F) of the base material 1. The base material 1 is composed of a heat-resistant alloy. Specific examples of the alloy include spring steel and martensitic stainless steel. The base material 1 may be a base material having a nitride layer formed on the surface.

[0039] The film 5 constitutes the sliding surface 10F. The film 5 is made of a Me-Si-N material (Me represents a metal element). The thickness of the film 5 is, for example, 5 to 70 μm, preferably 10 to 50 μm. By making the thickness of the film 5 5 μm or more, there is a tendency to improve the durability of the piston ring 10. On the other hand, by making the thickness of the film 5 70 μm or less, high productivity of the film 5 can be ensured.

[0040] The metal element Me is, for example, Cr, Ti, Al, Zr, Nb, etc. The amount of Me in the Me-Si-N system material is preferably 40 atomic % or more, more preferably 40 to 55 atomic %, and further preferably 45 to 52 atomic %. By making the amount of Me in the Me-Si-N system material be 40 atomic % or more, the characteristics of the metal element Me are fully reflected in the film 5. The Me-Si-N system material can contain one metal element or two or more metal elements. Among the above metal elements, Cr is preferred because the atomic radius is close to Si in solid solution.

[0041] The amount of Si in the film 5 is 1.1 to 7.5 atomic%, preferably 1.5 to 7.0 atomic%, and more preferably 2.0 to 5.0 atomic%. The film 5 having an Si amount of 1.1 atomic% or more is composed of fine grains and has excellent hardness. By making the Si amount in the film 5 less than 7.5 atomic%, it is easy to form an appropriate amount of amorphous phase in the film 5. It is speculated that the amorphous phase helps to suppress cracks. The amount of Si in the film 5 can be adjusted by the amount of Si in the target used when forming the film 5 using a physical vapor deposition method (PVD method).

[0042] The crystallite size of the film 5 is 10 to 30 nm, preferably 15 to 25 nm. When the crystallite size is 30 nm or less, even if the film 5 is worn, the unit of one wear is small, and the wear resistance is improved.

[0043] The compressive residual stress of the film 5 is 400 to 800 MPa. By setting the residual stress (compression) of the film 5 within the above range, the stress difference with the substrate 1 (alloy or nitride layer) can be reduced, thereby suppressing the peeling at the interface between the substrate 1 and the film 5. In addition, cracks in the film 5 that are easily generated by adding Si can be suppressed.

[0044] The crystal orientation of the film 5 preferably satisfies the following conditions for the microstructure coefficient of each crystal plane. By balancing the crystal orientation of the film 5, the progress of cracks can be inhibited, and the peeling of the film 5 due to the combination of cracks can be effectively prevented.

[0045] CrN(111): 0.4 or more (more preferably 0.6 to 1.2)

[0046] CrN(200): 1.0 or more

[0047] CrN(220): 0.5 or more

[0048] The hardness of the film 5 is preferably 1000HV0.1 to 1800HV0.1, and more preferably 1100HV0.1 to 1500HV0.1. The ratio H / E of the hardness H (GPa) of the film 5 obtained by the nanoindenter to the Young's modulus E (GPa) of the film 5 is preferably 0.04 to 0.07, and more preferably 0.05 to 0.06. By making the ratio H / E within the above range, the film 5 can be elastically deformed appropriately, thereby reducing the Hertz stress caused by sliding, and achieving excellent peeling resistance.

[0049] (Method for manufacturing piston ring)

[0050] Next, a description will be given of a method for manufacturing the piston ring 10. The manufacturing method of the present embodiment includes the following steps.

[0051] (a) A step of cleaning the surface of the substrate 1 .

[0052] (b) A step of forming a film 5 satisfying the following conditions by physical vapor deposition.

[0053] <Conditions of film 5>

[0054] The amount of Si is in the range of 1.1 to 7.5 atomic %.

[0055] The crystallite size is in the range of 10 to 30 nm.

[0056] ·Compressive residual stress is 400~800MPa.

[0057] Step (a) is a step for cleaning the surface of the substrate 1 before forming the film 5. For example, cleaning treatment by degreasing or shot blasting may be performed. Alternatively, blast cleaning may be performed in a chamber.

[0058] The formation of the film 5 in the step (b) can be implemented by physical vapor deposition. The formation of the film 5 is implemented after the chamber is filled with a nitrogen atmosphere. As physical vapor deposition methods, ion plating, sputtering, etc. can be listed. These physical vapor deposition methods are all implemented in a vacuum chamber, and the nitrogen pressure of the vacuum chamber is set to a range of 2 to 6 Pa. In addition, the bias voltage is set to a range of -5 to -18V.

[0059] By changing the amount of Si in the target, the amount of Si in the film 5 can be adjusted. The amount of Si in the film 5 can also be adjusted by supplying a Si-containing gas into the chamber. According to the amount of Si in the film 5, the hardness of the film 5 can be adjusted, and the crystal orientation and the crystallite size can be adjusted. These properties can also be adjusted by the temperature (film forming temperature) when the film 5 is formed. The film forming temperature can be, for example, below 550°C. The residual stress and hardness of the film 5 can be adjusted by adjusting the nitrogen pressure and bias voltage in the chamber.

[0060] In order to form a relatively soft film 5 even though the film 5 contains Si, at least one of the following conditions may be adopted.

[0061] The nitrogen pressure in the chamber is set high. The pressure is, for example, 4.0 to 6.0 Pa.

[0062] · The bias voltage (absolute value) is set to a small value. The bias voltage is, for example, -5 to -10V.

[0063] According to this manufacturing method, it is possible to manufacture the piston ring 10 having all sufficiently high levels of peeling resistance, crack resistance, and wear resistance.

[0064] Example

[0065] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples. The present invention is not limited to the following Examples.

[0066] As a base material of a piston ring, a ring having the following composition was prepared.

[0067] Fe: 80.4 mass%

[0068] C: 0.85 mass%

[0069] Cr: 17.0 mass%

[0070] ·Si: 0.5 mass%

[0071] Mn: 0.5 mass%

[0072] Other elements: margin

[0073] (Examples 1 to 9 and Comparative Examples 1 to 6)

[0074] The piston rings of the embodiment and the comparative example were respectively produced as follows. That is, first, the substrate was degreased and cleaned, and then placed in a chamber. Next, the substrate was bombarded and cleaned in the chamber. Then, a film (thickness: about 20 μm) was formed on the surface of the substrate by ion plating under the conditions shown in Table 1 and Table 2. It should be noted that the film forming temperature was set to 500°C. The arc current was set to 150A.

[0075] <Film Characteristics>

[0076] The properties of the films of the piston rings of Examples and Comparative Examples are shown in Tables 1 and 2. In addition, each property was measured by the following method.

[0077] (Si amount)

[0078] The Si content of the film was measured using EPMA (apparatus name: JXA-8100, manufactured by JEOL Ltd.) at an acceleration voltage of 15 kV and an irradiation current of 5.0 × 10 -8 A. Measurement was performed under the condition of a beam diameter of 10 μm. It should be noted that, from the X-ray diffraction data, it was determined that Si in the films of the Examples and Comparative Examples (except Comparative Example 4) was dissolved in solid.

[0079] (Crystal Orientation)

[0080] The crystal orientation of the film was evaluated by the structure coefficient of each crystal plane obtained from X-ray diffraction data using an X-ray diffraction device (device name: SmartLab, manufactured by Rigaku Corp.) The structure coefficient of each crystal plane was determined by the following formula.

[0081] Organization coefficient = [I(hkl) / I 0 (hkl)] / [Σ{I(hkl) / I 0 (hkl)} / n]

[0082] Where, I(hkl) is the measured X-ray diffraction intensity of the (hkl) plane, I 0 (hkl) is the standard X-ray diffraction intensity reported in the JCPDS file.

[0083] (Residual Stress)

[0084] The residual stress of the film was measured using an X-ray stress device (device name: PSPC micro-part X-ray stress measurement device, manufactured by Rigaku). Since the following relationship holds, the residual stress is calculated using the slope of the straight line between the diffraction angle 2θ and sin2ψ (ψ is the angle between the normal direction of the sample surface and the normal direction of the diffraction surface).

[0085]

[0086] Where K is the stress constant (obtained from Young's modulus, Poisson's ratio, and reflection angle θ in the unstrained state), using -762MPa. The measurement was carried out by the same inclination method under the conditions of Cr tube, voltage 35kV, current 40mA, collimator 1mm, ψ 6 points (0, 18, 27, 33, 39, 45 degrees), measurement time 90 seconds, diffraction angle CrN (311), 2θ = 132.86°. It should be noted that the negative sign in Table 1 and Table 2 refers to compressive residual stress.

[0087] (hardness)

[0088] The hardness of the film was obtained by conducting a hardness test at a test load of 0.98 N using a Vickers hardness tester (device name: HM-220, manufactured by Mitutoyo) based on the method specified in ISO6507.

[0089] (Hardness H and Young's modulus E)

[0090] The hardness H of the film obtained by the nanoindenter and the Young's modulus E of the film were obtained using an ultra-micro indentation hardness tester (device name: ENT-1100a, manufactured by Elionix). That is, based on the test method specified in ISO14577, a diamond indenter with a front end shape of a regular triangular pyramid (Berkovich type) was used to perform a hardness test under a test load of 0.4N, and the hardness was obtained based on the "load-displacement curve" obtained by the load applied to the indenter and the displacement of the indenter during the test.

[0091] (Crystallite size)

[0092] The crystallite size of the film was calculated using an X-ray diffraction device (device name: SmartLab, manufactured by Rigaku Corporation) using the following Scherrer equation on the CrN (200) plane.

[0093] Crystallite size = Kλ / βcosθ

[0094] Where K is the Scherrer constant, which is 0.94, and λ is the wavelength of the X-ray (Cu: ), β is the half-peak width, and θ is the Bragg angle.

[0095] <Sliding fatigue test>

[0096] As an accelerated wear test, use Figure 2 The testing machine of the structure shown is used to carry out sliding fatigue test. Figure 2 The test machine 50 shown in the figure has: a rotating drum 51, a mechanism for making a test piece S (piston ring cut piece) abut against the surface of the drum 51, a mechanism for repeatedly applying a load to the test piece S, and a mechanism for supplying lubricating oil to the sliding part. In this way, the test piece can be worn in a relatively short time. The test conditions are as follows.

[0097] Test load: 20~50N, sine curve (50Hz)

[0098] ·Target material (roller): SUJ2 heat-treated material (diameter 80mm)

[0099] Movement speed: forward and reverse trapezoidal mode operation

[0100] Lubricant: Base oil (add 0.1cc every 30 seconds)

[0101] ·Drum surface temperature: 80℃

[0102] Test time: 2 to 3 minutes per cycle, 5 cycles

[0103] <Evaluation>

[0104] 20 piston rings of each embodiment and comparative example were made, and 20 sliding fatigue tests were performed on them as evaluation objects. The peeling resistance and crack resistance of the film were evaluated by visually observing the film after the sliding fatigue test. The wear resistance was evaluated based on the wear amount of the film of comparative example 4. The evaluation criteria are as follows.

[0105] (Peel resistance)

[0106] A: Among 20 samples, the occurrence rate of peeling was 40% or less.

[0107] B: Among 20 samples, the occurrence rate of peeling was more than 40% and less than 80%.

[0108] C: Among 20 samples, the occurrence rate of peeling was 80% or more.

[0109] (Crack resistance)

[0110] A: Among 20 samples, the crack generation rate was 35% or less.

[0111] B: Among 20 samples, the crack generation rate was greater than 35% and less than 90%.

[0112] C: The crack generation rate was 90% or more among 20 samples.

[0113] (Abrasion resistance)

[0114] The wear amount when the wear amount of the conventional CrN film is set as 1.0

[0115] A: The wear amount is 0.7 or less.

[0116] B: The wear amount is greater than 0.7 and less than 0.9.

[0117] C: The wear amount is 0.9 or more.

[0118]

[0119] [Table 2]

[0120]

[0121] Industrial Applicability

[0122] According to the present invention, a piston ring provided with a film containing Si and N and having sufficiently high levels of peeling resistance, crack resistance and wear resistance can be provided, and a method for producing the same.

[0123] Explanation of symbols

[0124] 1…base material, 5…film, 10…piston ring, 10F…sliding surface.

Claims

1. A method for manufacturing a piston ring, comprising: (A) a step of cleaning the surface of a base material of a piston ring; as well as (B) forming a film containing Si and N by physical vapor deposition in a chamber so as to cover at least a portion of the surface of the substrate, In step (B), in order to form the film satisfying the following conditions, the pressure in the chamber is set within the range of 2 to 6 Pa, and the bias voltage is set within the range of -5 to -18 V, <Coating conditions> The amount of Si is in the range of 1.1 to 7.5 atomic %; ·The crystallite size is in the range of 10 to 30 nm; ·Compressive residual stress is 400~800MPa.

2. The method for manufacturing a piston ring according to claim 1, wherein: The hardness of the film is 1000 HV0.1 to 1800 HV0.

1.

3. A piston ring comprising a substrate and a coating containing Si and N and provided so as to cover at least a portion of a surface of the substrate, The membrane satisfies the following conditions: <Coating conditions> The amount of Si is in the range of 1.1 to 7.5 atomic %; ·The crystallite size is in the range of 10 to 30 nm; ·Compressive residual stress is 400~800MPa.

4. The piston ring according to claim 3, wherein: The film further contains Cr.

5. The piston ring according to claim 4, wherein: The amount of Cr in the film is 40 atomic % or more.

6. The piston ring according to claim 4 or 5, wherein: The microstructure coefficient of CrN (111) of the film is 0.4 or more.

7. The piston ring according to claim 3 or 4, wherein: The hardness of the film is 1000 HV0.1 to 1800 HV0.

1.

8. The piston ring according to claim 3 or 4, wherein: The ratio H / E of the hardness H (GPa) of the film and the Young's modulus E (GPa) of the film obtained by a nanoindenter is 0.04 to 0.07.

Citation Information

Patent Citations

  • Slide member and manufacturing method thereof

    JP2002266697A

  • Piston ring for internal-combustion engine

    JP2008014228A

  • Apparatus and method for adjusting colors among multiple color cameras

    JP2010016803A

  • Nitrogen-containing amorphous carbon film, amorphous carbon layered film, and sliding member

    JP2010070848A

  • Slide system

    JP2018150434A